2014
DOI: 10.1073/pnas.1411557111
|View full text |Cite
|
Sign up to set email alerts
|

Defects in T-tubular electrical activity underlie local alterations of calcium release in heart failure

Abstract: Action potentials (APs), via the transverse axial tubular system (TATS), synchronously trigger uniform Ca 2+ release throughout the cardiomyocyte. In heart failure (HF), TATS structural remodeling occurs, leading to asynchronous Ca 2+ release across the myocyte and contributing to contractile dysfunction. In cardiomyocytes from failing rat hearts, we previously documented the presence of TATS elements which failed to propagate AP and displayed spontaneous electrical activity; the consequence for Ca 2+ release … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
112
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(123 citation statements)
references
References 40 publications
8
112
3
Order By: Relevance
“…Measurement of AP propagation in the TATS is a quite recent possibility, achieved by combining random access two-photon microscopy and voltage imaging (11,35). In line with the above considerations, this methodology revealed that the majority of T-tubules properly propagate the AP, even in diseased cardiomyocytes (11)(12)(13)(14). However, these results do not exclude the presence of individual electrically failing tubules.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Measurement of AP propagation in the TATS is a quite recent possibility, achieved by combining random access two-photon microscopy and voltage imaging (11,35). In line with the above considerations, this methodology revealed that the majority of T-tubules properly propagate the AP, even in diseased cardiomyocytes (11)(12)(13)(14). However, these results do not exclude the presence of individual electrically failing tubules.…”
Section: Discussionmentioning
confidence: 94%
“…Finally, in view of the formal analogy that exists between diffusion and electrical conduction, the apparent diffusion coefficient is linked to the effective electrical conductivity of the network. The methodology is first validated using an acutely detubulated cellular model (8,9) and then applied to assessing the effective electrical conductivity in diseased cardiomyocytes where structural (10) and functional (11)(12)(13)(14)(15) defects of the TATS have been described.…”
Section: Significancementioning
confidence: 99%
“…This work has demonstrated, in myocytes from rats in which heart failure was induced by myocardial infarction, that there can be regions of apparently intact t-tubule that fail to propagate the action potential, resulting in delayed local Ca 2+ transient. Furthermore, in other t-tubular regions, spontaneous Ca 2+ release was found to trigger a local action potential (delayed after-depolarisation) that then, in turn, triggered a larger Ca 2+ release in the same region, indicating a role of t-tubules in arrhythmic events common in heart failure (Crocini et al 2014). To what extent these different mechanisms arising from t-tubule remodelling contribute to the development of heart failure remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The t-tubules are an extension of the sarcolemma (Soeller and Cannell 1999) and provide a signalling pathway for the rapid propagation of the action potential deep within the myocyte interior, within milliseconds, facilitating a synchronous cell-wide Ca 2+ release that is much faster and larger than if the cell relied on Ca 2+ diffusion from initiation events at the cell surface (Kawai et al 1999;Cordeiro et al 2001;Brette et al 2002Brette et al , 2006Louch et al 2004;Sacconi et al 2012). For example, a typical Ca 2+ transient in rat myocytes with intact t-tubules reaches its peak Ca 2+ within ∼60 milliseconds; if the t-tubules are removed by osmotic shock-induced detubulation with formamide, peak Ca 2+ is reached much later, in ∼120 milliseconds (Crocini et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Light provides the versatility required to develop and test customized stimulation patterns capable of successfully interrupting arrhythmias at much lower energy. We exploit recent advancements in optogenetics [6][7][8] and imaging techniques 9,10 to develop a novel optical platform capable of simultaneously mapping and controlling the electrical activity of whole hearts with sub-millisecond temporal resolution. An ultra-fast laser scanning system is used to design arbitrarily-chosen stimulation patterns across the whole heart.…”
mentioning
confidence: 99%